59.0k views
5 votes
Using suitable algebraic identities, find the value of
2004^2 - 2003^2 + 2002^2 - 2001^2

1 Answer

5 votes


(x+1)^2-x^2=(x^2+2x+1)-x^2=2x+1

Let
x=2003. Then


2004^2-2003^2=(2003+1)^2-2003^2=2\cdot2003+1=4007

Similarly, if
x=2001, then


2002^2-2001^2=2\cdot2001+1=4003

So


2004^2-2003^2+2002^2-2001^2=4007+4003=8010

Alternatively, you can consider the larger expression


(x+3)^2-(x+2)^2+(x+1)^2-x^2

Expanding each binomial product gives


(x^2+6x+9)-(x^2+4x+4)+(x^2+2x+1)-x^2=4x+6

Then if
x=2001, we get


2004^2-2003^2+2002^2-2001^2=4\cdot2001+6=8010

User Hemu
by
6.0k points